Death of Boa constrictor amarali (serpentes, boidae) after ingestion of a tree porcupine (rodentia) - Cherubini,A. L. (2003)
The objective of this paper is to report the death of a Boa constrictor amarali after ingestion of a tree porcupine. The animal was donated to the Center for the Study of Venoms and Venomous Animals (CEVAP/UNESP) - and died in captivity. At necropsy, spine-like structures were observed in the stomach serosa and vicinity, and the stomach mucosa showed an intense reddish area, suggesting inflammation. The analysis of the spine-like structure revealed that they were tree porcupine spines. The feeding habits and inexperience of this Boa constrictor amarali in selecting its prey may have been be responsible for its death.